Study of the Status of Medical Students and Residents' Thesis in Kerman University of Medical Sciences in Terms of Contribution to Scientific Development - Fatemeh Karami Robati; Tahereh Alinaghi; Ali Hosseininasab; Mohammad Mahdi Hayatbakhsh Abbasi (Kerman University of Medical Sciences, 2019)
Background Dissertations or theses are valuable sources of information, which play an important role in scientific development because of their specific nature and characteristics. Objectives The aim of this study was to investigate the status of medical students and residents' dissertations in terms of contribution to scientific development in Kerman University of Medical Sciences. Methods This cross-sectional, analytical study examined the status of medical students and residents' dissertations, submitted to the Medical Faculty of Kerman University of Medical Sciences during 2012 - 2015. First, the research deputy of Kerman University of Medical Sciences provided the dissertation information. Then, the information was analyzed in terms of study design, study type, extraction of Persian and English articles, publication in domestic and international journals, and indexing in reputable scientific databases in two groups of medical students and residents' dissertations. SPSS was used for all statistical analyses. Results In total, 643 dissertations were studied, including 342 (53%) residents and 301 (47%) medical students' thesis. Overall, 267 (41.5%) dissertations were published as articles in domestic and international journals. The findings showed that 13.4% of articles were indexed in the Scopus database. The mean scores of medical students and residents' dissertations were 19.22 ± 0.70 and 19.15 ± 0.85, respectively. Conclusions Despite the large number of medical students and residents' dissertations submitted to Kerman University of Medical Sciences, a limited number of dissertations were published as scientific and research papers, and the number of articles indexed in international journals was insignificant. Thesis writing is generally a unique opportunity for students to learn research skills and methods. In addition, publication of thesis findings in domestic and international databases can lead to scientific development.